Chronic obstructive pulmonary disease is independently associated with hypertension in men: A survey design analysis using nationwide survey data. Issue 19 (May 2017) - Kim, Seon-Hye; Park, Ju-Hee; Lee, Jung-Kyu; Heo, Eun Young; Kim, Deog Kyeom; Chung, Hee Soon
Abstract : Abstract: Although studies have shown that chronic obstructive pulmonary disease (COPD) and hypertension are linked as comorbidities, it remains unclear whether COPD is independently associated with the risk of hypertension or is caused by common risk factors such as age and smoking. The objective of this study was to investigate the relationship between COPD and hypertension by using nationally representative data. This cross-sectional study analyzed data from the Korea National Health and Nutrition Examination Survey V conducted during 2010 to 2012. Hypertension was defined as a mean systolic blood pressure ≥ 140 mm Hg and/or a diastolic blood pressure ≥ 90 mm Hg, or current consumption of antihypertensive medications. A diagnosis of COPD was defined as a smoking history of at least 10 pack-years with airflow limitation on spirometry. Multivariate logistic regression was performed to investigate the independent association between COPD and hypertension after adjusting for covariates. Survey design analyses were conducted for all analyses. Among 4043 men (aged ≥ 40 years) who underwent spirometry, 2190 (54.2%) had hypertension. Even after adjusting for age, body mass index, smoking status, diabetes, metabolic syndrome, and stroke, COPD was independently associated with hypertension (adjusted odds ratio, 1.71; 95% confidence interval, 1.37–2.13; P  < .001). Adjusted pulse pressure significantly increased as the ratio of forced expiratory volume in 1 s (FEV1) to forced vital capacity and FEV1 decreased. COPD is independently associated with hypertension, and this could explain the link between the risk of cardiovascular diseases and COPD.